2022
DOI: 10.1186/s12911-022-02020-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel signature model based on mitochondrial-related genes for predicting survival of colon adenocarcinoma

Abstract: Background Colon cancer is the foremost reason of cancer-related mortality worldwide. Colon adenocarcinoma constitutes 90% of colon cancer, and most patients with colon adenocarcinoma (COAD) are identified until advanced stage. With the emergence of an increasing number of novel pathogenic mechanisms and treatments, the role of mitochondria in the development of cancer, has been studied and reported with increasing frequency. Methods We systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Cui Tang’ research results showed that HOXB13 plays a tumor-promoting role in HCC cells, promotes HCC drug resistance by up-regulating CDC25C, and improves the ability of cells to resist anoikis 45 . These studies found that CDC25C may be an important target gene in patients with COAD because they are related to metabolism, cell cycle and tumor progression 46 , 47 . Mariana Toricelli found that Timp1 confers cell survival through activation of the PDK1 pathway and that Timp1 and AKT cooperate to confer resistance to anoikis in metastatic melanoma cells 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Cui Tang’ research results showed that HOXB13 plays a tumor-promoting role in HCC cells, promotes HCC drug resistance by up-regulating CDC25C, and improves the ability of cells to resist anoikis 45 . These studies found that CDC25C may be an important target gene in patients with COAD because they are related to metabolism, cell cycle and tumor progression 46 , 47 . Mariana Toricelli found that Timp1 confers cell survival through activation of the PDK1 pathway and that Timp1 and AKT cooperate to confer resistance to anoikis in metastatic melanoma cells 48 .…”
Section: Discussionmentioning
confidence: 99%
“… 16 Gao et al has made the first attempt to identify multi-gene markers of mitochondria-related genes and evaluate their potential function in COAD. 17 However, we constructed the prognostic model for COAD containing these nine genes at the first time. Our results, which showed OS has a greater AUC value at 1, 3 and 5 years, seem to have better prognostic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the role of mitochondria-associated genes in predicting COAD prognosis are still insufficient. 17 Alterations in mitochondrial metabolic pathways may impact colon cancer cell proliferation and invasion. 43 We focused on researching mitochondria-associated genes and innovatively discovered nine biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced mitochondrial dysfunction can inhibit cancer cell proliferation and metastasis (Jiaqi et al, 2023). Moreover, there is growing evidence indicating that some mitochondria‐related genes (e.g., AREG and CCND1) can predict the prognosis of cancer patients (Gao & Xing, 2022; Li et al, 2023).…”
Section: Introductionmentioning
confidence: 99%